Charter of the CGIAR System Organization—Amended 1 October 2024 - CGIAR System Management Office (CGIAR, 2024)
This Charter was agreed between the CGIAR System’s Funders and 15 Centers on 16 June 2016 and with effect from 1 July 2016 as the governing instrument of the CGIAR System Organization.